Logging In and Staying On: Exploring Immersive Virtual Influencers and How They Drive Consumers' Immersive Time - Henrietta Batinovic; Fabian Tingelhoff; Maik Hammerschmidt; Sofia Schöbel (Journal of Consumer Behaviour, 2025)
This study explores the role of virtual influencers (VIs) as critical touchpoints for enhancing consumers' “Immersive Time (ImT)”—the time spent on virtual reality-empowered immersive platforms. By blurring the lines between virtual and physical-world experiences, immersive platforms transform VIs into “Immersive Virtual Influencers (IVIs)” with enhanced functional capabilities. In this paper, we first assess the nature and extent of consumers' ImT with IVIs. Second, using the affordance perspective, we investigate how IVI design elements impact consumers' expectations of IVIs' functions and, in turn, ImT. Employing a mixed-method approach, our initial survey ( N 0.167em=0.167em179) uncovers that consumers so far only spend limited ImT with IVIs and identifies reasons hindering prolonged engagement. Our following qualitative analysis, based on 30 semi-structured interviews, reveals distinct pathways to enhance ImT for two consumer segments: potential and incumbent users of immersive platforms. For instance, potential users seek an idealized utopia, exemplified by IVIs designed to appear flawless. Conversely, incumbents view immersive platforms as an extension of physical reality, represented by IVIs that embrace greater diversity. By unpacking the nuanced drivers of ImT, we construct a framework on consumer-specific expectations regarding IVI functions. The framework informs about the strategic design and functions of IVIs imperative to fostering a more engaging and prolonged virtual experience for different consumer segments. Thus, we contribute to the burgeoning discourse on how immersive platforms alter consumer behavior and offer guidance for brands on how to navigate the complex dynamics of immersive influencer marketing.
Keywords: 320; affordance perspective; consumer experiences; immersive platforms; immersive time; virtual influencers